2016
DOI: 10.1080/15384047.2016.1177676
|View full text |Cite
|
Sign up to set email alerts
|

The p38 MAPK inhibitor BIRB796 enhances the antitumor effects of VX680 in cervical cancer

Abstract: VX680 is a potent and selective inhibitor that targets the Aurora kinase family. The p38 mitogen-activated protein kinase (MAPK) regulates a large number of cellular pathways and plays an important role in the regulation of cell survival and apoptosis. This study aimed to evaluate the effect of VX680 on cervical cancer cells and investigate whether the effects on apoptosis are enhanced by the ablation of p38 MAPK activation. The results suggested that VX680 inhibited the proliferation of cervical cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 58 publications
3
30
0
1
Order By: Relevance
“…It has recently been shown that the MAPK pathways are targets for development for therapeutic agents against cervical cancer [44]. Recently, it has been shown that methyl protodioscin (MPD) induces apoptosis by increasing the levels of phosphorylated JNK and p38 pathway [45].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that the MAPK pathways are targets for development for therapeutic agents against cervical cancer [44]. Recently, it has been shown that methyl protodioscin (MPD) induces apoptosis by increasing the levels of phosphorylated JNK and p38 pathway [45].…”
Section: Discussionmentioning
confidence: 99%
“…For thymidine-taxol, cells were synchronized via double-thymidine blockade and released into taxolcontaining medium (0.1 μM). Cell-cycle distributions were analyzed via flow cytometry as previously described [29] .…”
Section: Cell Synchronization and Cell Cycle Assaysmentioning
confidence: 99%
“…MAPK (p38) inhibitor has been demonstrated antitumor effect on cervical, gastric and colon cancer [27][28][29]. Ralimetinib, an oral MAPK (p38) inhibitor, was currently performed first-in-human phase I pharmaceutical clinical trial in advanced cancers [30].…”
Section: Discussionmentioning
confidence: 99%